1987
DOI: 10.1042/bj2420081
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonic analogues of tyrosine and 3,4-dihydroxyphenylalanine (dopa) influence mushroom tyrosinase activity

Abstract: A series of phosphonic analogues of tyrosine and 3,4-dihydroxyphenylalanine (dopa) were synthesized in order to study their interaction with mushroom tyrosinase. 1-Amino-2-(3,4-dihydroxyphenyl)ethylphosphonic acid and 1-amino-2-(3,4-dimethoxyphenyl)ethylphosphonic acid turned out to be substrates for mushroom tyrosinase with Km values of 3.3 mM and 9.3 mM respectively. Shortening of the alkyl chain by one methylene group gave amino-(3,4-dihydroxyphenyl)methylphosphonic acid, one of the most powerful known inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…Notably, the latter can provide convenient access [15] to important phosphorus analogues of phenylalanine (A), tyrosine (B) or DOPA (C). [16] In this full account we report a detailed study of the application of phosphane-phosphite (P-OP) ligands to the enantioselective hydrogenation of enol-ester phosphonates in studies including the synthesis of new ligands and catalyst precursors, supplemented with X-ray and NMR structural data for pertinent rhodium complexes. Part of this work has been published in a preliminary form.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the latter can provide convenient access [15] to important phosphorus analogues of phenylalanine (A), tyrosine (B) or DOPA (C). [16] In this full account we report a detailed study of the application of phosphane-phosphite (P-OP) ligands to the enantioselective hydrogenation of enol-ester phosphonates in studies including the synthesis of new ligands and catalyst precursors, supplemented with X-ray and NMR structural data for pertinent rhodium complexes. Part of this work has been published in a preliminary form.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most potent, competitive inhibitors include mimosine [5,6], tropolone [7,8], and kojic acid [9–12]. Some of us had previously shown that amino‐(3,4‐dihydroxyphenyl)methylphosphonic acid, the phosphonic analog of 3,4‐dihydroxyphenylglycine, was also a potent inhibitor of tyrosinase [13]. With a K i of 50 and 97 µ m for tyrosine and Dopa as substrates, respectively, it was comparable with mimosine and tropolone.…”
mentioning
confidence: 99%
“…Most investigations on interactions of phosphonic acid derivatives with tyrosinase reported in the literature [38][39][40] regards structures which are analogs of tyrosinase natural substrates: L-Tyrosine and L-DOPA and they contain phenolic or diphenolic moiety. Some of the compounds acted as tyrosinase new substrates and some revealed moderate inhibitory activity.…”
Section: Discussionmentioning
confidence: 99%